Efeito imediato da mobilização ântero-posterior do tálus na amplitude de dorsiflexão em indivíduos com disfunção ortopédica do tornozelo e do pé - Luciana Mundim Teixeira (2011)
The anteroposterior mobilization of the talus is broadly used in physical therapy practice. Few researches have investigated the effect of this therapy in the dorsiflexion range of motion (ROM) of subjects with different foot and ankle injuries. The objective of this research was to determine the immediate effect of anteroposterior mobilization of the talus on active dorsiflexion ROM in subjects with different foot and ankle injuries. Thirty subjects were analysed in this study, including both sexes. Subjects ages were between 18 and 50 years old with unilateral orthopedic foot and ankle injury. All subjects underwent three series of active dorsiflexion ROM measurement in both ankles. Measurements included baseline,post-first treatment and post-second treatment measures. All subjects received articular mobilization or manual contact (control) at the affected ankle. Active dorsiflexion ROM was assessed through the biplane goniometer with subjects in prone position and 90º of knee flexion. The results showed that both treatments (articular mobilization or manual contact) increased active dorsiflexion ROM. However, the average difference of dorsiflexion pre and post mobilization was higherthan pre and post control. Therefore, only one anteroposterior mobilization of the talus wasnt enough to statistically increase dorsiflexion ROM in subjects with different foot and ankle injuries. We concluded that the increase in dorsiflexion ROM occurs due to cumulative effect. Therefore, it is necessary a greater number of interventions to reach a statistically significant effect.